2016
DOI: 10.1051/shsconf/20162902026
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental sources of individual differences in non-verbal intelligence in Russian adolescents

Abstract: Abstract. Current study aimed to estimate the impact of genetic and environmental factors in the individual differences in non-verbal ability in Russian adolescents. The sample included 580 twins. Nonverbal ability was assessed by means of Standard Raven's Progressive Matrices. Individual differences in non-verbal ability were explained almost entirely by family environment (65%) and person-specific environment (29%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Explanations for the low heritability, suggested by the authors, included assortative mating (which masks heritability through making DZ twins more similar to each other) and features of parenting, such as parental involvement in children's education. Consistent with Gene-Gini interplay, the authors also discussed as a potential explanation the lower socioeconomic status of families and associated decrease in gene-environment processes, as well as inequality-related increase in environmental variance (Malykh et al, 2016;Voronin et al, 2016).…”
Section: Birth Cohorts Within and Across Countriesmentioning
confidence: 83%
See 1 more Smart Citation
“…Explanations for the low heritability, suggested by the authors, included assortative mating (which masks heritability through making DZ twins more similar to each other) and features of parenting, such as parental involvement in children's education. Consistent with Gene-Gini interplay, the authors also discussed as a potential explanation the lower socioeconomic status of families and associated decrease in gene-environment processes, as well as inequality-related increase in environmental variance (Malykh et al, 2016;Voronin et al, 2016).…”
Section: Birth Cohorts Within and Across Countriesmentioning
confidence: 83%
“…In contrast, low heritability was found after the reforms of the 1990s. One study of 580 twins in Russia examined the heritability of non-verbal ability (measured by Standard Raven's Progressive Matrices) in adolescents aged 10-14 years born in the mid-1990s (Malykh et al, 2016). Both MZ and DZ twins were highly similar, suggesting that individual differences in non-verbal ability were explained almost entirely by family environment (65%) and person-specific environment (29%), with minimal genetic effects (6%).…”
Section: Birth Cohorts Within and Across Countriesmentioning
confidence: 99%
“…Shared environmental sources of the variation in nonverbal intelligence are largely twin-specific: the study of twin and sibling pairs from Russia Ivan Voronin, Psychological Institute of Russian Academy of Education; Sergey Malykh, Psychological Institute of Russian Academy of Education; Tatiana Tikhomirova, Psychological Institute of Russian Academy of Education Our previous research on Russian adolescent twins revealed a substantial shared environmental variation in the individual differences in the non-verbal ability (65%, Malykh et al 2016), unlike the other behavior genetic research of cognitive abilities (30%, Polderman et al 2015). The current study aimed to estimate the role of twin-specific shared environmental effects by comparing twin and sibling pairs.…”
Section: Multi-ancestry Meta-analysis and Ld Score Regressionmentioning
confidence: 99%